Irrigation and Water Management Research in CGIAR: What Do We Know of the Impacts? - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2015)
A significant proportion of CGIAR research investment has been spent on policy and natural resource management (NRM). However, compared with other areas of research e.g., crop germplasm improvement (CGI), there appear to be relatively few impact assessments (IAs) in this domain. To fill this gap, one of the activities of the Standing Panel on Impact Assessment (SPIA)-coordinated Strengthening Impact Assessment in the CGIAR (SIAC) program (http://impact.cgiar.org/work-program/siac) targets assessments of these presumably ‘under-evaluated areas’ of CGIAR research (http://impact.cgiar.org/impacts/under-evaluated-areas), including irrigation and water management, agroforestry and policy and social sciences. This brief summarizes the findings and recommendations of a critical review of IAs of CGIAR irrigation and water management research (full report) (http://impact.cgiar.org/sites/default/files//pdf/Merrey_Irrigation_IAs_review.pdf).